EFFECT OF WORK ENVIRONMENT, WORK STRESS AND COMPENSATION ON EMPLOYEE WORK PRODUCTIVITY: (STUDY STUDY AT PT SAMUDERA INDONESIA LAMPUNG BRANCH) - Afriliani, Riska; Bhakti, Dadang Karya; Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine the effect of the work environment, work stress and compensation on the work productivity of PT.Samudera Indonesia Tbk employees. This research was conducted on employees of PT.Samudera Indonesia Tbk with a sample of 45 respondents, the sample technique used is simple random sampling, The type of research used is explanatory quantitative and uses descriptive data analysis, multiple linear regression test, classical assumption test, and hypothesis testing using software SPSS 23 for windows evaluation version. The results of this study indicate that the work environment variable has a positive and significant effect on the performance of PT.Samudera Indonesia Tbk employees, the work stress variable has a positive and significant effect on the performance of PT.Samudera Indonesia’s employees and the compensation variable has a positive and significant effect on the performance of PT.Samudera Indonesia Tbk employees .